Distribution, Density and Swarming Periods of Homoeosoma nebulellum (Den. & Schiff.) Harmfull on Sunflower in Ankara Province - YÜCEL, Cenk; ÇOBANOĞLU, Sultan (MAS Journal of Applied Sciences, 2022)
In the sunflower, which is an important oilseed and confection plant (Helianthus annuus L.), a studywas conducted in 2013-2014 in Ankara province in order to determine the distribution and density ofHomoeosoma nebulellum (Den. & Schiff.) which causes lost in terms of quality and quantity. The data wereobtained from surveys in Ayaş, Bala, Beypazarı and Kalecik districts where sunflower was found intensively. Inthe same period, the adult flights in Kalecik district were observed by the delta-type traps containing an sexualattractive pheromone and the period that the pest was harmful in the sunflower was determined. As a result ofthe study, H.nebulellum was recorded as 94.37-100% widespread in Ayas, Kalecik, Bala and Beypazarı districts.In 2013, the infestation rate of pest in the sunflower fields were determined by 4.77%, 7.51, 4.76 and 1.09 inAyaş, Kalecik, Bala and Beypazarı districts, respectively. In 2014, decreasing infestation rates were determinedexcept Beypazarı district and the rates were recorded as 3.73%, 6.45, 3.15 and 1.40, respectively. The density ofthe pest in the infestated fields were 8.08, 9.93, 2.75 and 6.56 piece larvae/infestated plant in Kalecik, Bala andBeypazarı districts in 2013, respectively. In 2014, it was determined as 2.87, 5.66, 3.08 and 2.25 piece larvae /infestated plant respectively. H. nebulellum larvae was determined as causing yield loss by feeding in newlyformed sunflower seeds. By monitoring swarming periods of European sunflower moth, seasonal swarmingperiods were determined. As a result of the study, the situation of pest in Ankara was observed and the criticalperiod, which is important for management was determined by monitoring with pheremon traps.